Learn programming framework for Malaysian preschoolers - Laura P. Jack; Norazlina Khamis; Carolyn Salimun; Dinna M. Nizam; Zaidatol Haslinda Abdullah Sani; Aslina Baharum (The World Academy of Research in Science and Engineering, 2019)
Learning computer programming is a good way to develop Computational Thinking, but many students assumed that computer programming is a complicated subject, which leads toward their disinterest in computer science. We believe that this assumption can be overcome if the students were introduced to the concept of programming earlier during preschool years. The best programming method for children to learn programming is the tangible programming method but current Malaysian preschool syllabus does not contain a framework for preschoolers to learn tangible programming. This paper introduces the developmentally-appropriate Learn Programming Framework (LPF) for preschoolers to learn programming concepts. The structured syllabus in LPF involves a series of controlled-play activities to be used with the novel tangible board game. Once the framework has been successfully implemented, extensive evaluation of LPF will be done to test its effectiveness in teaching children about programming